Associations among socioeconomic status, patterns of care and outcomes in breast cancer patients in a universal health care system: Ontario's experience. Issue 6 (22nd December 2015) - Kumachev, Alexander; Trudeau, Maureen E.; Chan, Kelvin K. W.
Abstract : BACKGROUND: The Canadian health care system provides equitable access to equivalent standards of care. The authors investigated to determine whether patients with breast cancer who had different socioeconomic status (SES) received different care and had different overall survival (OS) in Ontario, Canada. METHODS: Women who were diagnosed with breast cancer between 2004 and 2009 were identified from the Ontario Cancer Registry and linked to provincial databases to ascertain patient demographics, screening, diagnosis, treatment patterns, and survival. SES was defined as neighborhood income by postal code and was divided into income quintiles (Q1‐Q5; with Q5 the highest SES quintile). Univariable and multivariable analyses were used to examine the associations between: 1) SES and mammogram screening and breast cancer treatments, and 2) SES and OS. RESULTS: In total, 34, 776 patients with breast cancer who had information on disease stage available at diagnosis were identified. Seventy‐six percent of women were aged >50 years. Patients with higher SES were more likely to be diagnosed at an earlier stage (Q5 [44.3%] vs Q1 [37.7%]; odds ratio [OR], 1.31; 95% confidence interval [CI], 1.23‐1.41; P < .0001) and also were more likely to receive adjuvant chemotherapy (Q5 vs Q1: OR, 1.18; 95% CI, 1.10‐1.26; P < .0001) and radiotherapy (Q5 vs Q1: OR, 1.24; 95% CI, 1.15‐1.33; P < .0001). The 5‐year OS rates for Q1 through Q5 were 80%, 81%, 82.2%, 83.9%, and 85.7%, respectively ( P < .0001). After adjusting for patient demographics, cancer stage at diagnosis, adjuvant chemotherapy, trastuzumab, radiotherapy and surgery types, higher SES remained associated with better OS ( P = .0017). CONCLUSIONS: In a universal health care system, higher SES is associated with greater screening and treatments and with better OS after adjusting for screening, cancer stage at diagnosis, and treatments. Cancer 2016;122:893–8 . © 2015 American Cancer Society . Abstract : Higher socioeconomic status is associated with increased receipt of screening and treatments in patients with breast cancer in Ontario, Canada. In addition, higher socioeconomic status is associated with improved overall survival even after adjusting for screening, cancer stage at diagnosis, and treatment patterns.